Studies on the Efficiency of the Impact of Paraffin Inhibitors on Lowering the WAT Temperature and Reducing the Amount of Paraffin Deposit - Szuflita, Sławomir; Pajda, Michał; Kuśnierczyk, Jerzy; Wojnicki, Mirosław; Warnecki, Marcin (Energies (Basel), 2020)
This paper discusses the issues of the impact of pressure and temperature on the precipitation of paraffin deposits from reservoir fluids in the presence of previously prepared paraffin inhibitors. Using a properly modified PVT apparatus, the temperature of the beginning of paraffin precipitation (wax appearance temperature—WAT) has been determined, below which the solid paraffin phase was captured on a specialized filter in various temperatures. Based on the conducted experiments, a boundary has been established separating the paraffin area (the presence of paraffins as their solid phase) from an area without paraffin. Measurements of the amount of paraffin using the filter allowed the determination of the WPC (wax precipitation curve), due to which additional data is provided regarding the amount of precipitated paraffin deposit below the WAT. The developed methodology enables to conduct the measurements within a wide range of pressures using the sample saturated with reservoir gas, which can test the crude oil sample that corresponds to the actual production conditions. Most known research methods do not allow such preparation of a sample and conducting the measurements under pressurized conditions; therefore, the produced results are subject to errors. The paper describes also the studies of efficiency and differences in the action of various paraffin inhibitors. Based on the performed research, a comparison was made involving the action of agents under the pressureless conditions of dead oil and pressurized crude oil samples saturated with gas. The performed studies allowed the determination of equilibrium conditions (in a pressure–temperature system), under which deposition of the solid paraffin phase occurs during the use of three various inhibitors. Based on the performed experiments, an area with a paraffin hazard was determined, along with an area without paraffins. Due to the separation of the precipitated solid paraffin phase, an increase in the mass of the paraffin deposit associated with a temperature drop was determined (wax precipitation curve), as well as the impact of the applied inhibitors on its course.